Analysis of dust on the parameters of PV module and design of an effective solar dust cleaner - Arjyadhara Pradhan; Babita Panda; Lipika Nanda; Chitralekha Jena (Institute of Advanced Engineering and Science, 2022)
Photovoltaic panel output is affected by various factors like solar isolation, temperature, dust, shading, mounting. Among all these factors dust is a prominent factor which greatly reduces panel efficiency. With increase in the quantity of dust both efficiency and power output of the module reduces. As the mass of dust deposition increases, power output and the efficiency of the module decreases. Dust particles are of different shapes and sizes. PV panels installed on ground or roof top are subjected to dust all the time. The amount and type of dust deposition depends on tilt angle, locations, surroundings nearby, rainfall pattern of that area, maintenance method of the installer. PV plant nearby any industry giving out lot of fumes and smokes will have heavy dust deposition over its top surface. Similarly, PV plants located near areas where roads are not concrete can cause dust deposition on its panels. Manual maintenance is labor costing and less efficient. In this work we have performed dust analysis on the performance of PV panel and designed an effective method to clean the panel and make it dust free. Solar dust cleaner and cooler system provides a solution for both dusts cleaning and keeping the panels at less temperature.